Anxiety disorders and CRP in a population cohort study with 54, 326 participants: The LifeLines study. (18th August 2018) - Naudé, Petrus J. W.; Roest, Annelieke M.; Stein, Dan J.; de Jonge, Peter; Doornbos, Bennard
Abstract: Objectives: Growing evidence indicates that inflammatory processes may play a role in the pathogenesis of anxiety disorders. Nevertheless, much remains to be learned about the involvement of inflammation, including C-reactive protein (CRP), in specific anxiety disorders. This study examines the relation between anxiety disorders and CRP. Methods: Associations of serum CRP with anxiety disorders were determined in a large population study ( n = 54, 326 participants, mean age = 47 years; 59% female), the LifeLines cohort. Depressive and anxiety disorders (generalized anxiety disorder, social anxiety phobia, panic disorder with or without agoraphobia and agoraphobia without panic disorder) were assessed using the Mini-International Neuropsychiatric Interview. Results: Anxiety disorders, with the exception of social anxiety disorder, were significantly associated with increased CRP. After adjusting for demographics, life style factors, health factors, medication use, depression, and psychological stressors, CRP remained significantly associated with panic disorder with agoraphobia (β = 0.01, P = .013). Moreover, CRP levels were significantly higher in people with panic disorder with agoraphobia compared to other anxiety disorders, independent of all covariates ( F = 3.00, df = 4, P = .021). Conclusions: Panic disorder with agoraphobia is associated with increased CRP, although the effect size of this association is small. This indicates that neuroinflammatory mechanisms may play a potential role in its pathophysiology.